Analisis Structural Equation Modelling (SEM) Pengaruh Kepuasan Kerja, Lingkungan, Work Life Balance, Kompetensi dan Komitmen Pegawai Terhadap Kinerja - Abdillah, Muhammad Afwan; Nugroho, Sukmo Hadi (Universitas Trunojoyo Madura, 2024)
Employee performance is an important factor for companies operating in the public service sector, especially in water treatment companies, where their services cover the interests of many people. This research was conducted to see the influence of job satisfaction, work life balance, work environment, employee commitment and employee competency on employee performance in water treatment companies in Bekasi Regency, where there are still few researchers who have conducted research in water treatment companies, so we hoped that this research can become an additional reference for researchers who will choose similiar companies as the object of their research. The research was carried out using a survey method and using questionnaires as its tool, questionnaires were distributed online and face to face to employees within the Water Treatment Companies in Bekasi Regency. The distribution of the questionnaire was carried out in December 2023 with a total of 151 respondents. To test the hypothesis, the data obtained from the questionnaire was then analyzed using the SEM-PLS method. The research results show that the work environment, work life balance and employee competency have positive influence toward employee performance at Water Treatment Companies in Bekasi Regency.